Research on the Construction of Indonesian Chinese Language Acquisition Case Resource Based on Building Learning Communities - Wei, Yangyang (Universitas Negeri Malang, 2024)
Acquisition case resources, as integrated accounts of experiences from Chinese learners, serve as high-quality resources for Indonesians to understand Chinese language and culture, thereby contributing to the construction of a local Chinese language learning community in Indonesia. Ultimately, they inject new vitality and momentum into the co-construction of the